2019
DOI: 10.1111/iej.13225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immersion in distilled water or phosphate‐buffered saline on the solubility, volumetric change and presence of voids within new calcium silicate‐based root canal sealers

Abstract: Aim To assess the effect of immersion in distilled water or phosphate‐buffered saline (PBS) on the solubility, volumetric change and presence of voids of calcium silicate‐based root canal sealers (TotalFill BC, Sealer Plus BC and Bio‐C), in comparison with the gold standard epoxy resin‐based sealer (AH Plus). Methodology All properties were evaluated after immersion in distilled water or PBS. Solubility was determined by the percentage of mass loss, whereas volumetric change and presence of voids were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
106
0
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(136 citation statements)
references
References 28 publications
16
106
0
14
Order By: Relevance
“…3,16 Since gutta-percha is considered a dimensionally stable material, 17 this thin film of sealer is considered more favorable in the case of sealers presenting solubility above the values recommended by the ISO 6876:2012 standard, such as Bio-C. 22,32 Nevertheless, a great amount of sealer is expected when the single-cone technique is used. 5,16 The suitable filling of the flattened areas when Bio-C Sealer and the thermoplastic technique were used could be attributed to the low percentage of voids and good flow values of Bio-C. 22,32 These results may be related to the small size of the calcium silicate-based sealer particles (smaller than 2 µm). 1,17 AH Plus is an epoxy resin-based sealer considered the gold standard regarding physical properties 33 , and is used in different studies together with thermoplastic filling techniques.…”
Section: Resultsmentioning
confidence: 99%
“…3,16 Since gutta-percha is considered a dimensionally stable material, 17 this thin film of sealer is considered more favorable in the case of sealers presenting solubility above the values recommended by the ISO 6876:2012 standard, such as Bio-C. 22,32 Nevertheless, a great amount of sealer is expected when the single-cone technique is used. 5,16 The suitable filling of the flattened areas when Bio-C Sealer and the thermoplastic technique were used could be attributed to the low percentage of voids and good flow values of Bio-C. 22,32 These results may be related to the small size of the calcium silicate-based sealer particles (smaller than 2 µm). 1,17 AH Plus is an epoxy resin-based sealer considered the gold standard regarding physical properties 33 , and is used in different studies together with thermoplastic filling techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In the Torres et al study, after immersion in distilled water, all calcium silicate-based cements had high solubility values [22]. The values after immersion in phosphate-buffered saline were significantly lower compared to immersion in water, in any case the values were higher than the minimum required according to ISO 6876.…”
Section: Chemical-physical Propertiesmentioning
confidence: 84%
“…Many studies have been proposed the use of micro-CT for the evaluation of endodontic materials [ 1 3 4 12 20 21 22 ]. Micro-CT allows a nondestructive, quantitative and qualitative high-resolution imaging-based assessment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to evaluate the filling ability of Bio-C. However, a previous study showed a low percentage of voids for this sealer, even after immersion in distilled water or phosphate buffered saline [ 22 ]. Moreover, the scanning resolution of the micro-CT images is fundamental for small voids detection.…”
Section: Discussionmentioning
confidence: 99%